2006
DOI: 10.1529/biophysj.105.066092
|View full text |Cite
|
Sign up to set email alerts
|

A Ca2+-Binding Domain in RyR1 that Interacts with the Calmodulin Binding Site and Modulates Channel Activity

Abstract: A fragment of RyR1 (amino acids 4064-4210) is predicted to fold to at least one lobe of calmodulin and to bind Ca(2+). This fragment of RyR1 (R4064-4210) was subcloned, expressed, refolded, and purified. Consistent with the predicted folding pattern, R4064-4210 was found to bind two molecules of Ca(2+) and undergo a structural change upon binding Ca(2+) that exposes hydrophobic amino acids. R4064-4210 also binds to RyR1, the L-type Ca(2+) channel (Cav(1.1)), and several synthetic calmodulin binding peptides. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“…Although RLC phosphorylation is typically associated with potentiation, this phosphorylation persists when fatigue begins (MacIntosh et al, 1993). The same Ca 2+ -calmodulin complex that activates MLCK also inhibits Ca 2+ release (Boschek et al, 2007;Xiong et al, 2006). The muscle is capable of decreasing the release of Ca 2+ , while 2+ ATPase in the membranes of the sarcoplasmic reticulum.…”
Section: Regulation Of the Interaction Between Actin And Myosinmentioning
confidence: 99%
See 2 more Smart Citations
“…Although RLC phosphorylation is typically associated with potentiation, this phosphorylation persists when fatigue begins (MacIntosh et al, 1993). The same Ca 2+ -calmodulin complex that activates MLCK also inhibits Ca 2+ release (Boschek et al, 2007;Xiong et al, 2006). The muscle is capable of decreasing the release of Ca 2+ , while 2+ ATPase in the membranes of the sarcoplasmic reticulum.…”
Section: Regulation Of the Interaction Between Actin And Myosinmentioning
confidence: 99%
“…At rest, when [Ca 2+ ] is low, calmodulin exists in the apocalmodulin (apoCaM) form, and upon increase in [Ca 2+ ] i binds to Ca 2+ , becoming Ca 2+ -bound (CaCaM), and resulting in a change of its shape and its effect as a ligand (Boschek et al, 2007;Boschek et al, 2008;Xiong et al, 2006). At low [Ca 2+ ] i (up to 0.1 mM), the Ca 2+ -free apoCaM binds to RyR and increases its P o .…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the EF-hand Ca 2ϩ binding domain (residues 4064 -4210 in RyR1) may interact with the calmodulin-binding domain (residues 3614 -3643 in RyR1) and regulate the response of the channel to Ca 2ϩ and calmodulin (12). We have shown recently that calmodulin modulates the termination of SOICR by increasing the SOICR termination threshold in a Ca 2ϩ -dependent manner (12,35). Therefore, it is conceivable that the EFhand Ca 2ϩ binding domain may regulate the activation and termination of SOICR by interfering with the action of calmodulin.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gomez and Yamaguchi (11) have also shown that the EF-hand Ca 2ϩ binding domain in RyR1 is involved in Ca 2ϩ -dependent inactivation. Furthermore, a peptide that encompasses the EF1 and EF2 motifs has been found to bind to the intact RyR1 channel and altered the Ca 2ϩ dependence of [ 3 H]ryanodine binding (12 Recently, the three-dimensional structure of RyR1 has been solved at near-atomic resolutions by using cryo-electron microscopy and single particle analysis (13)(14)(15). These highresolution structures have provided unprecedented insights into the structure-function relationship of Ca 2ϩ regulation of RyR.…”
mentioning
confidence: 99%